Popliteal sciatic nerve block versus intrathecal anesthesia for Achilles tendon rupture repair surgery: a mono-centric retrospective comparative study - Si, Gao; Wang, Liwei; Deng, Minzhi; Sun, Yihan; Cao, Yuan; Fan, Jixing; Zhu, Tengjiao; Tian, Yun; Lv, Yang; Wu, Changyi (Frontiers in Medicine, 2025)
BackgroundTo compare the anesthetic and analgesic effects of popliteal sciatic nerve block and intrathecal anesthesia in acute Achilles tendon rupture patients undergoing surgery.MethodsThis retrospective cohort study analyzed 115 patients with acute Achilles tendon rupture who underwent surgery at Peking University Third Hospital between May and November 2023. After excluding cases lost to follow-up or declining participation, 96 patients were ultimately enrolled. Patients were divided into two groups based on the different anesthesia methods they received: the popliteal sciatic nerve block group (BG) and the spinal anesthesia group (SAG). The anesthesia effects intraoperatively were compared between the two groups using puncture satisfaction, immediate complications of puncture, anesthesia operation time, and puncture pain evaluation. Postoperative analgesic and anesthesia recovery effects were compared between the two groups using visual analog scale (VAS), analgesic satisfaction score, sleep score, and time to complete sensory recovery. Ankle joint mobility was used to compare postoperative motor recovery between the two groups.ResultsStatistical analysis revealed that in terms of anesthesia effectiveness, the BG had a shorter anesthesia operation time (1.95 ± 0.40 min) than the SAG (7.44 ± 1.90 min), and the BG (5.4%) had fewer immediate puncture complications than the SAG (25.0%). Regarding analgesic effectiveness, the BG (4.10 ± 0.09) had higher analgesic satisfaction compared to the SAG (3.14 ± 0.11), and within 48 h postoperatively, wound VAS scores in the BG were consistently lower than those in the SAG. Postoperatively, the time for complete sensory recovery in the affected lower limb in the BG (9.29 ± 0.41 h) was significantly longer than that in the SAG (6.09 ± 0.42 h).ConclusionCompared to intrathecal anesthesia, the use of popliteal sciatic nerve block (PSNB) in Achilles tendon repair surgery resulted in shorter anesthesia operation time, fewer immediate puncture complications, higher patient satisfaction with analgesia, and longer duration of analgesic effect. PSNB may be preferred for reduced complications and prolonged analgesia.